Analyses of the scholarly and scientific output from grants funded by the Danish Council for Independent Research from 2005 to 2008 - Schneider, Jesper Wiborg; Bloch, Carter Walter; Aagaard, Kaare; Degn, Lise; Haase, Sanne; Henriksen, Dorte; Calero-Medina, Clara; van Wijk, Erik (CFA Scientific Reports, 2014)
The purpose of the present report is to examine the output and citation impact of publications reported as outcomes of various types of grants funded by the Danish Council for Independent Research (DFF) in the period 2005 to 2008. The results presented in the report are based upon state-of-the-art bibliometric indicators calculated on meticulously assembled comprehensive and unique datasets. While the data still has a number of limitations, which we describe in detail in this report, both quality and completeness of the data are high by international standards and form a strong basis for the analyses in this report.